Helicobacter Pylori (Hp) Infection Among Healthy Blood Donors And Endoscoped Patients In Northern Peninsular Malaysia. - Uyub, A.M.; Sasidharan, S.; Ahmad Azlan, A.A. (2001)

(untitled)
Over a 9-month period, sera from 5370 healthy blood donors were investigated for anti-HP IgG and anti-HP IgA antibodies. Seroprevalence for HP infection was 14.2%. There was no significant difference between the prevalence rate across all races and both sexes.